Discover Command Utterance in Missing (2023) Movie: Directive Illocutionary Act - Asih, Ni Kadek Agustina Yunita; Dian Puspita Candra, Komang (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p05, 2024)
This study aims to analyze command in directive illocutionary acts and the types and intentions of the command depending on the context found in the movie entitled Missing (2023). This qualitative quantitative research applies the theory proposed by Searle & Vanderveken (1985) for data analysis. In presenting the data, this study used formal and informal methods. The result shows that the amount of command in directive illocutionary act is 63 utterances with the details: utterance by June 17 (27%), Dad 13 (21%), Mom 12 (19%), Police 7 (11%), Veena 3 (5%), US Embassy 3 (5%), Javi 3 (5%), Kevin 2 (3%), Girl 1 (2%), Gomes 1 (2%), 911 Dispatcher 1 (2%). June as the main character becomes a person with the most frequently utters Command Directive Illocutionary Act in this movie.